Proteção constitucional contra a dispensa arbritária do empregado: do descumprimento à efetividade - Oyama Karyna Barbosa Andrade (2012)
This dissertation focuses on constitutional protection against unjustifiedtermination of employment contract in Brazil. We first analyze the evolution of legal systems concerning employment contract, particularly the decennial stability and the Fundo de Garantiapor Tempo de Serviço (FGTS), and, more recently, the model brought by the 1988 Constitution. Based upon the neoconstitutionalist approach, José Afonso da Silvas theory on the application of constitutional normsand Labor Lawliterature, we conclude that this model is currently being disobeyed. It is then discussed the International Labor Organizations Convention concerning termination of employment at the initiative of the employer (n. 158), which guarantees, in International Law, the principle of protection against unjustified dismissal. We next demonstrate that,due to its contents and history of its ratification and denunciation, the Convention is fully compatible to Brazilian Constitution and is valid, since its denunciation was invalid. The following chapter addresses the matter of collective redundancies, which have been discussed publicly and in Courts since the occurrence of such episodes after the 2008world economic crisis. In the third part, the conclusions of this research are presented, pointing out to possible solutions in order to effectively protect workers against unjustified dismissals. We propose a systematic interpretation of the 1988 Constitution, which values the fundamental rights of worker people.